PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN SUBSEKTOR ADVERTISING, PRINTING, DAN MEDIA - Lia Amalia; Asep Rokhayadi (Departemen Manajemen, 2020)
Intellectual Capital Towards Financial Performance of Advertising, Printing and Media Subsector Companies Listed on the Indonesia Stock Exchange in 2015-2018.. This study uses a purposive sampling method, from 17 manufacturing companies in the Advertising, Printing and Media sub-sectors,, the samples are in accordance with 13 companies. Data collection in this research was carried out by taking secondary data collected through idx.co.id. The intellectual capital component was developed by using the Value Added Intellectual Capital Coefficient (VAIC ™) developed by Pulic..The company's performance uses profitability ratios, namely Return on Assets (ROA) using the Multiple Linear Regression analysis method..This study results that the Value Added of Human Capital (VAHU) has a positive and significant effect on financial performance..While for Value Added Capital Employed (VACE) has a negative and significant effect on financial performance, Value Added Capital Structure (VASC) has a positive and not significant effect. However, VAIC has a positive and significant influence on the Financial Performance of the Advertising, Printing and Media Subsectors Listed on the Indonesia Stock Exchange in 2015-2018